Single crystal structure, solid state characterization and dissolution rate of terbinafine hydrochloride - Kuminek, Gislaine (2013)
Terbinafine hydrochloride (TH), a poorly water soluble antifungal agent, was characterized by solid state techniques including differential scanning calorimetry, thermogravimetry, X-ray powder diffraction, optical and electron microscopies, Fourier transform infrared, Raman and solid-state nuclear magnetic resonance spectroscopies and intrinsic dissolution rate (IDR). A colorless single crystal of TH was grown from an ethanol:water solution and its crystalline structure was determined through X-ray single crystal diffraction. Also, a new crystal habit of TH was obtained through the slow solvent evaporation technique revealing a needle-like shape. A comparison between the IDR results for the TH raw material and TH needle-like crystal revealed lower values for the new crystal habit, which can be attributed to the preferential orientation of the crystals in the compressed disks.